2013
DOI: 10.3758/s13421-013-0376-8
|View full text |Cite
|
Sign up to set email alerts
|

Is naming faces different from naming objects? Semantic interference in a face- and object-naming task

Abstract: A current debate regarding face and object naming concerns whether they are equally vulnerable to semantic interference. Although some studies have shown similar patterns of interference, others have revealed different effects for faces and objects. In Experiment 1, we compared face naming to object naming when exemplars were presented in a semantically homogeneous context (grouped by their category) or in a semantically heterogeneous context (mixed) across four cycles. The data revealed significant slowing fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Given the fact that RIF depends on competition, our results are in line with data showing semantic competition (Brédart & Valentine, 1992;Darling & Valentine, 2005;Marful, Paolieri, & Bajo, 2014) by showing not only interference in face naming, but also that this interference is solved by means of inhibitory mechanisms. Furthermore, these data support models of facial recognition proposing that competition can arise at several levels of representation (Brédart et al, 1995;Bruce & Young, 1986;Burton et al, 1990Burton et al, , 1999.…”
Section: Discussionsupporting
confidence: 91%
“…Given the fact that RIF depends on competition, our results are in line with data showing semantic competition (Brédart & Valentine, 1992;Darling & Valentine, 2005;Marful, Paolieri, & Bajo, 2014) by showing not only interference in face naming, but also that this interference is solved by means of inhibitory mechanisms. Furthermore, these data support models of facial recognition proposing that competition can arise at several levels of representation (Brédart et al, 1995;Bruce & Young, 1986;Burton et al, 1990Burton et al, , 1999.…”
Section: Discussionsupporting
confidence: 91%
“…Studies using the blocked-cyclic naming paradigm differ with respect to the presentation of lists to participants. While some have used a random (Schnur et al, 2006) or an alternating order (e.g., Belke et al, 2005b), others feature a blocked presentation of lists by contexts (e.g., Abdel Rahman and Melinger, 2007; Crowther and Martin, 2014; Marful et al, 2014). …”
Section: Evidence For Strategic Facilitation In Cyclementioning
confidence: 99%
“…Proper name retrieval appears to be more complex in comparison to object name retrieval. In fact, compared to object name retrieval, proper name retrieval is slower and more error prone (e.g., [ 27 , 32 ]). To explain the causes for these face-naming difficulties, Fogler and James [ 33 ] pointed out the existence of several characteristics that could make this category of words more complex than the rest, amongst which are their lower frequency, lower imaginability, and phonological complexity.…”
Section: Introductionmentioning
confidence: 99%
“…However, both the effect of aging and the effect of proper name retrieval in this paradigm have been much less studied and, to the best of our knowledge, the joint effects of aging and face naming have never been explored. Thus, with respect to face naming in the semantic-blocking paradigm, Marful et al [ 32 ] found that semantic interference was present for both faces (proper name retrieval) and objects (common name retrieval), suggesting that semantic information is processed in similar ways for both types of stimuli during this task. Regarding aging, the few studies using semantic blocking have yielded contrasting results [ 52 54 ].…”
Section: Introductionmentioning
confidence: 99%